(untitled) (Fiep Bulletin - online, 2012)
The purpose of this study is to identify in Lima Barreto’s chronicles the charges and criticisms that the man of letters commented against soccer in early 20th Century. We will use Lima Barreto chronicles’ clippings analyzing them in the social and political context of the three first post-republic decades. The study has identified that Lima Barreto’s criticisms were due to the fact and soccer served as an instrument of workers’ dissension, Republic maneuvering strategies and establishing the eugenics process made official by the post-republican Government.